The adventures of Huckleberry Finn [videorecording (DVD)] - Thorpe, Richard, 1896-1991; Rooney, Mickey; Connolly, Walter, 1887-1940; Frawley, William, 1887-1966; Ingram, Rex, 1895-1969; Carver, Lynne, 1909-1955; Twain, Mark, 1835-1910 (WB Home Entertainment Group archive collection, 2009)
Eager to flee from his drunken father and the confining life with Widow Douglass and Miss Watson, Huck sets off on a raft down the Mississippi with Jim, a runaway slave, in tow.